2012
DOI: 10.1146/annurev-economics-080511-110939
|View full text |Cite
|
Sign up to set email alerts
|

The Promises and Pitfalls of Genoeconomics

Abstract: This article reviews existing research at the intersection of genetics and economics, presents some new findings that illustrate the state of genoeconomics research, and surveys the prospects of this emerging field. Twin studies suggest that economic outcomes and preferences, once corrected for measurement error, appear to be about as heritable as many medical conditions and personality traits. Consistent with this pattern, we present new evidence on the heritability of permanent income and wealth. Turning to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
206
2
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 188 publications
(228 citation statements)
references
References 110 publications
10
206
2
1
Order By: Relevance
“…Researchers studying gene-by-environment (G E) interactions must wrestle with a number of conceptual and de…nitional questions (Benjamin et al 2012b;Chow and Lee 2012) and empirical challenges (Conley 2009). In molecular genetic work, a major challenge is that most genetic e¤ects on complex outcomes, including political variables, are likely to be of tiny magnitude (Benjamin et al 2012a, b).…”
Section: B the Interaction Of Pre-birth And Post-birth Factorsmentioning
confidence: 99%
“…Researchers studying gene-by-environment (G E) interactions must wrestle with a number of conceptual and de…nitional questions (Benjamin et al 2012b;Chow and Lee 2012) and empirical challenges (Conley 2009). In molecular genetic work, a major challenge is that most genetic e¤ects on complex outcomes, including political variables, are likely to be of tiny magnitude (Benjamin et al 2012a, b).…”
Section: B the Interaction Of Pre-birth And Post-birth Factorsmentioning
confidence: 99%
“…This enthusiasm is based on a number of potential contributions that such research could make to social science (1)(2)(3). For example, if specific genetic markers can be identified that are associated with a behavioral trait, then such predictive markers may shed light on the biological pathways underlying that trait (3,4).…”
mentioning
confidence: 99%
“…Parents, for example, are likely to modify the environment in response to their children's genetic endowments. This implies that estimates from behavioral genetics models are difficult to interpret because they are essentially reduced-form estimates from a more general model in which environmental influences are endogenous with respect to genotype (see Beauchamp et al 2011, Benjamin et al 2012 for a discussion). Using such estimates for policy development requires a great deal of caution.…”
Section: Behavioral Geneticsmentioning
confidence: 99%
“…Benjamin et al (2008) coined the phrase "genoeconomics" to refer to the use of molecular genetic information in economics. Two primary research strategies are being used to identify the link between genes and behavior: i) candidate gene studies in which an "educated guess" is used to select particular genes for analysis because of their known biological functions; and ii) genome-wide association studies (GWAS) in which researchers look for associations between the outcome of interest and millions of possible genetic variations across the human genome (see Benjamin et al 2012). …”
Section: Genoeconomicsmentioning
confidence: 99%
See 1 more Smart Citation